Analisis Pengendalian Kualitas Produk Beras dengan Menggunakan Metode Statistical Quality Control di Penggilingan Beras Nabila Putri - Abdul Aziz; Rudy Effendi Listyanto; Mukhlisin Mukhlisin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Product quality is an important factor in the rice milling industry because it affects consumer satisfaction and product selling value. Nabila Putri Rice Mill still faces quality problems in the form of crushed rice (groats) and unpeeled rice. This study aims to identify the factors causing product defects and analyze the implementation of quality control using the Statistical Quality Control (SQC) method. The method used is Statistical Quality Control (SQC) with the help of Seven Tools, namely check sheets, histograms, Pareto diagrams, control charts (P-Charts), and fishbone diagrams. Research data were obtained through observation and documentation of the production process during the period October–November 2025. The results showed that the total rice production was 98,114 kg with the number of defects amounting to 1,011 kg or 1.03% of total production. The Pareto diagram shows that the dominant defect is crushed rice (groats) amounting to 92.28% of the total defects. The P-Chart results show that the production process is within the statistical control limits. Fishbone analysis shows that the causes of defects come from machine, method, material, and human factors. After the proposed improvements were implemented, the number of defects decreased from 1,011 kg to 837 kg, a 17% decrease. Based on the research results, the SQC method proved effective in identifying the causes of defects and assisting quality control, thereby reducing the number of defective products in the rice production process at the Nabila Putri Rice Mill.